Soil Chemical and Biological Characteristics for Diagnostic the Potency of Acid Dry Land for Soybean Extensification - . Prihastuti; . Sudaryono (JOURNAL OF TROPICAL SOILS, 2013)
The descriptive explored study was conducted in districts Bumi Nabung, Sari Bakti, Seputih Banyak and Rumbia, Central Lampung, Indonesia. The parameters observed consisted of chemical and biological aspects of soil, which directly affected plant growth. This activity was carried out as preliminary studies for the diagnosis of soybean extensification on acid dry land. The results showed that all locations observed were less suitable for soybean development, indicated by low pH values (4.35 – 6.00), nutrient contents (N < 0.1% and C-organic < 2.0%), and low soil microbial populations. Population of bacteria was 17 × 103 – 29 × 104 CFU g-1 soil and fungi was 21 × 101 – 63 ×102 CFU g-1 soil of soils. Beneficial microbe types included non-symbiotic nitrogen-fixing bacteria (with the capability to fix the Nitrogen around 0.16 – 1.53 mM 100 ml-1 medium h-1), phosphate solubilizing bacteria (with the value index 1.22 – 6.25) and arbuscular mycorrhizal fungi (with root colonization by 70.50 – 90.33% and the number of sporeswere 49 – 175 spores g-1 soil). This less suitable land can be improved to become suitable for developing soybean by using innovative technology. Soil biological and chemical improvement technology through liming and amelioration as well as organic and bio-fertilizers applications were required for soybeans extensification on acid dry land.[How to Cite: Prihastuti and Sudaryono. 2013. Soil Chemical and Biological Characteristics for Diagnostic the Potency of Acid Dry Land for Soybean Extensification. J Trop Soils, 18 (1) : 17-24. doi: 10.5400/jts.2013.18.1.17][Permalink/DOI: www.dx.doi.org/10.5400/jts.2013.18.1.17]